2016
DOI: 10.1021/acs.jpcc.6b11187
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Fluoroborate Laser Glasses by Solid State NMR and EPR Spectroscopies

Abstract: The structure of glasses in the systems (100 – x)­B2O3–xPbF2 (x = 30, 40, and 50) and 50B2O3–(50 – x)­PbO–xPbF2 (x = 5, 10, 15, 20, 25, 30, 35, 40, and 45) has been studied by solid state NMR and EPR spectroscopies. On the basis of 11B and 19F high resolution solid state NMR as well as on 11B/19F double resonance results, we develop a quantitative structural description on the atomic scale. 19F NMR results indicate a systematic dependence of the fluoride speciation on PbF2 content: At low x-values, F– ions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 69 publications
(159 reference statements)
4
33
0
Order By: Relevance
“…The site-selective REDOR dephasing curves are shown in part (b), obtained by systematically increasing the dipolar evolution time. The steep curvature observed in the initial part of the REDOR curve of F2 species indicates that B-bonded F species exist . However, the F1 signals exhibit a less dephasing effect owing to the remote dipolar interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The site-selective REDOR dephasing curves are shown in part (b), obtained by systematically increasing the dipolar evolution time. The steep curvature observed in the initial part of the REDOR curve of F2 species indicates that B-bonded F species exist . However, the F1 signals exhibit a less dephasing effect owing to the remote dipolar interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The F2 signal should be attributed to F−B linkages, as confirmed by 19 F{ 11 B} REDOR and 11 B{ 19 F} J-HMQC methods below. The Y-free glass was prepared to assist in the assignment of these 19 58 However, the F1 signals exhibit a less dephasing effect owing to the remote dipolar interaction. The accurate quantitative estimation of the B−F species is difficult because the remote-distance 11 B− 19 F interaction contributes a lot to the REDOR dephasing.…”
Section: Resultsmentioning
confidence: 99%
“…Glass structure is hard to be comprehensively characterized due to the disorder arrangement of atoms and the low resolution of traditional techniques. The solid‐state nuclear magnetic resonance (SSNMR) technique is a powerful tool to characterize the hyperfine structure of glass materials . Pulse electron paramagnetic resonance (EPR) technique is an effective way to investigate the local environment of rare‐earth (RE) ions.…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state nuclear magnetic resonance (SSNMR) technique is a powerful tool to characterize the hyperfine structure of glass materials. 15,16 Pulse electron paramagnetic resonance (EPR) technique is an effective way to investigate the local environment of rare-earth (RE) ions. Yu Yue et al 12 showed that the content of 31 P located in the second-order shell of Nd 3+ ions increased as P/Al ratio increased in Al 2 O 3 -P 2 O 5 -K 2 O glasses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation